Immunotherapy in Autoantibody-Associated Psychiatric Syndromes in Adults - Hansen, Niels; Timäus, Charles (Frontiers in Psychiatry, 2021)
Background: Autoantibody-associated psychiatric syndromes are often distinct from, but might also be part of autoimmune encephalitis. Our article focuses on potential immunotherapy in these patients with a probable autoimmune origin of their psychiatric syndrome. Methods: We searched through PubMed for appropriate articles on immunotherapy in autoantibody-associated psychiatric syndromes between 2010- 2020 for this narrative review. Results: In line with prior recommendations for autoimmune encephalitis and autoimmune psychosis, we suggest that in patients with a probable autoimmune-based psychiatric syndrome should be given early corticosteroids, intravenous immunoglobulins, or plasmapheresis as first line immunotherapy. If these therapeutic options fail, second-line immunotherapy should be applied within one month consisting of rituximab or cyclophosphamide. Maintenance therapy is best for those patients responding to steroids including mycofenolate mofetil or azathioprine. So far, there is evidence from a few retrospective cohort studies supporting the usage of first- and second-line, and maintenance immunotherapies for autoantibody-associated psychiatric syndromes. Some immunological agents are discussed that might exert an effect in autoimmune-based psychiatric syndromes, but the latest evidence is low and derived from case reports or series with autoimmune encephalitis patients. Conclusions: Taken together, the immunotherapeutic landscape for patients with autoantibody-associated psychiatric syndromes is delineated. Our suggestions rely on observational studies in autoantibody-associated psychiatric syndromes and a few placebo-controlled, randomized trial for patients with autoimmune encephalitis and psychosis. Thus, adequate powered, prospective as well as placebo-controlled clinical trials in patients with autoantibody-associated psychiatric syndromes are warranted in order to enlighten efficacy and safety aspects of current and novel therapy strategies.